The Influence of Trust on Consumer Purchase Behavior: Examining the Second-Hand Furniture Market in Cauayan City, Isabela - Lopez, Maria Cristy Felipa (Journal of Interdisciplinary Perspectives, 2025)
This study evaluated the influence of trust on consumer purchase behavior in online and physical secondhand furniture stores, aiming to identify the key trust factors that bolstered consumer confidence in each setting. Affordability and sustainability drove the growth of the secondhand furniture industry; however, customer trust significantly influenced purchasing behavior, especially in online transactions. Many consumers are unwilling to purchase used furniture due to concerns regarding product authenticity, inconsistent return policies, and inadequate transparency. Challenges such as complicated return processes, unreliable sellers, and deceitful products significantly impeded their purchase decisions. By acknowledging the impact of trust on consumer assurance, businesses could deal with these obstacles effectively. This study employed a quantitative approach to gather data from 200 consumers who had previously purchased secondhand furniture. The collected data underwent examination using descriptive statistics, correlation analysis, and regression analysis. The results indicated that in online shopping, the foremost aspect was delivering exceptional customer care. Seller reputation, delivery reliability, clarity of product information, and trust in payment methods were further critical aspects. However, the confidence in the return system obtained the lowest rating, reflecting customer apprehension. The study on physical stores revealed that past purchases, transparent pricing, and the store's reputation were the primary sources of trust. In addition, the product quality and the workers' expertise were important. On the other hand, the return policies and the atmosphere of the store had a negligible effect. It is important to note that trust plays a crucial role in individuals' decision-making process. To build a solid foundation of trust, secondhand furniture stores must be open and honest with their consumers about their pricing, return policies, and product details. Trust would help the pre-owned furniture sector to be more profitable and to please consumers more.